CATIA V5R19 for designers - Tickoo, Sham; Ekbote, S. (Cadcim Technologies, 2009)
Introduces the reader to CATIA V5R18, one of the world's leading paratmetric solid modeling packages. In this textbook, the author emphasizes the solid modeling techniques that improve the productivity and efficiency of the user. The chapters in this book are structured in a pedagogical sequence that make it very effective in learning the features and capabilities of the software. The following are some useful features of this book: Tutorial approach ; Real-world projects as tutorials ; Coverage of all important workbenches ; Tips and notes ; Heavily illustrated text ; Learning objectives ; Self-evaluation test, review questions, and exercises.